Pathways for Extracellular Fenton Chemistry in the Brown Rot Basidiomycete Gloeophyllum trabeum - Jensen, Kenneth A. (American Society for Microbiology, 2001)
The brown rot fungus Gloeophyllum trabeum uses an extracellular hydroquinone-quinone redox cycle to reduce Fe(3+) and produce H(2)O(2). These reactions generate extracellular Fenton reagent, which enables G. trabeum to degrade a wide variety of organic compounds. We found that G. trabeum secreted two quinones, 2,5-dimethoxy-1,4-benzoquinone (2,5-DMBQ) and 4,5-dimethoxy-1,2-benzoquinone (4,5-DMBQ), that underwent iron-dependent redox cycling. Experiments that monitored the iron- and quinone-dependent cleavage of polyethylene glycol by G. trabeum showed that 2,5-DMBQ was more effective than 4,5-DMBQ in supporting extracellular Fenton chemistry. Two factors contributed to this result. First, G. trabeum reduced 2,5-DMBQ to 2,5-dimethoxyhydroquinone (2,5-DMHQ) much more rapidly than it reduced 4,5-DMBQ to 4,5-dimethoxycatechol (4,5-DMC). Second, although both hydroquinones reduced ferric oxalate complexes, the predominant form of Fe(3+) in G. trabeum cultures, the 2,5-DMHQ-dependent reaction reduced O(2) more rapidly than the 4,5-DMC-dependent reaction. Nevertheless, both hydroquinones probably contribute to the extracellular Fenton chemistry of G. trabeum, because 2,5-DMHQ by itself is an efficient reductant of 4,5-DMBQ.